A Real-Time Application for Road Conditions Detection based on the Internet of Things - Sitanayah, Lanny; Angdresey, Apriandy; Kristalino, Evander (JOIV : International Journal on Informatics Visualization, 2022)
Bad road conditions may lead to road accidents, especially when drivers are unaware of potholes. The presence of potholes can increase from time to time and may get worse due to road age and bad weather. With the Internet of Things technology, vehicles on the road can be a means of collecting road condition data, such as vibration. The raw vibration data are useful only after they are processed into meaningful information. Information about the condition of roads can help other road users be aware of potholes. This paper proposes an Internet of Things application for road conditions detection. We design and implement a device comprising one NodeMCU ESP8266, one accelerometer gyroscope sensor to detect the existence of potholes based on the amount of detected vibration, and a GPS module to get the information about potholes' locations. For the web service, we use REST API so that users can get real-time potholes' information in the Android application. To cluster potholes based on detected vibration, i.e., deep, medium, and shallow, we implement the k-means clustering algorithm with k = 3. The Android application utilizes a Google map to visualize potholes' locations and the result of clustering on a road map. We use colored pins to indicate the depth of potholes. Deep potholes are shown on the map using red pins, medium potholes using orange pins, and shallow potholes using green pins.